Factors Influencing Team and Task Performance in Intensive Care Teams in a Simulated Scenario. Issue 1 (February 2021) - Jonsson, Karin; Hultin, Magnus; Härgestam, Maria; Lindkvist, Marie; Brulin, Christine
Abstract : Introduction: Healthcare teams and their performance in a complex environment such as that of intensive care units (ICUs) are influenced by several factors. This study investigates the relationship between team background characteristics and team as well as task performance. Methods: This study included 105 professionals (26 teams), working at the ICUs of 2 hospitals in Northern Sweden. The team-based simulation training sessions were video recorded, and thereafter, team performance and task performance were analyzed based on ratings of the TEAM instrument and the ABCDE checklist. Results: The final analyses showed that a higher age was significantly associated with better total team performance (β = 0.35, P = 0.04), teamwork (β = 0.04, P = 0.04), and task management (β = 0.04, P = 0.05) and with a higher overall rating for global team performance (β = 0.09, P = 0.02). The same pattern was found for the association between age and task performance (β = 0.02, P = 0.04). In addition, prior team training without video-facilitated reflection was significantly associated with better task performance (β = 0.35, P = 0.04). On the other hand, prior team training in communication was significantly associated with worse (β = −1.30, P = 0.02) leadership performance. Conclusions: This study reveals that a higher age is important for better team performance when caring for a severely ill patient in a simulation setting in the ICU. In addition, prior team training had a positive impact on task performance. Therefore, on a team level, this study indicates that age and, to some extent, prior team training without video-facilitated reflection have an impact on team performance in the care of critically ill patients.